If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -2(3x + 5) + -5x = 4 + -1(4 + -2x) Reorder the terms: 4 + -2(5 + 3x) + -5x = 4 + -1(4 + -2x) 4 + (5 * -2 + 3x * -2) + -5x = 4 + -1(4 + -2x) 4 + (-10 + -6x) + -5x = 4 + -1(4 + -2x) Combine like terms: 4 + -10 = -6 -6 + -6x + -5x = 4 + -1(4 + -2x) Combine like terms: -6x + -5x = -11x -6 + -11x = 4 + -1(4 + -2x) -6 + -11x = 4 + (4 * -1 + -2x * -1) -6 + -11x = 4 + (-4 + 2x) Combine like terms: 4 + -4 = 0 -6 + -11x = 0 + 2x -6 + -11x = 2x Solving -6 + -11x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -6 + -11x + -2x = 2x + -2x Combine like terms: -11x + -2x = -13x -6 + -13x = 2x + -2x Combine like terms: 2x + -2x = 0 -6 + -13x = 0 Add '6' to each side of the equation. -6 + 6 + -13x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -13x = 0 + 6 -13x = 0 + 6 Combine like terms: 0 + 6 = 6 -13x = 6 Divide each side by '-13'. x = -0.4615384615 Simplifying x = -0.4615384615
| 6=-3x+4x+4 | | -49=-7/9y | | 4v/3=-16 | | -7/5u=35 | | 4(a+2)+3(a+3)=10 | | 5-4(2x+6)=5(2-x)-3x | | Tbc=0 | | y^2+y=1 | | 6/1/3/8 | | 40*.8= | | 1/6x3= | | x+x+6+3x=36 | | 9/x=-6 | | (3/2x)-(2/3)=(7/4)-(1/3x) | | 4v-7=9(v-3) | | -2(u-5)=-4u+8 | | -8y-6=9(y+5) | | 8(x+8)-2x=22 | | 3(v-6)+6v=-36 | | 30=6(w+3)-4w | | 7-6y=33 | | 20-6y=33 | | 10a-7=73 | | 10a-7=72 | | 10a-7=78 | | 10a-2=48 | | 5x+7x-2x= | | 3(3d-5)=2(d+8) | | 5x-4-4x-13=20 | | 3x+4=3x+10 | | t+14=34-37 | | -6(x-9)=-8x+44 |